Overcoming depression a self-help guide using cognitive behavioral techniques - Gilbert, Paul 1951 June 20- (London Robinson, an imprint of Constable & Robinson Ltd, 2000)
This book provides a guide to recovering from sadness, loss and depression. It explains how the mind and body interact and how our thinking affects our brains. Case histories are used to show how others have overcome their problems.
What is depression? -- Causes of depression : biology and stress -- Causes of depression : how evolution may have shaped depression -- Causes of depression : early life, psychological and social aspects -- Initial steps -- Thoughts and feelings -- Challenging negative thoughts and feelings -- Styles of negative thinking -- Self-bullying and how to challenge it -- Calling ourselves names : how negative label affect us -- Further methods to challenge negative thoughts -- Approval, subordination and bullying -- Confronting shame -- Coping with guilt and caring too much -- Coping with anger -- From anger to assertiveness and forgiveness -- Dealing with frustrations, disappointments and lost ideals -- Perfectionism and competitiveness, or how the secret of success is the ability to fail -- Summing up.
Includes bibliographical references and index.
Keywords: Depression, Mental -- Popular works; Depression, Mental -- Treatment -- Popular works; Cognitive therapy -- Popular works; Cognitive therapy